Rancangan Perumahan dan Interaksi Penghuni dengan Sekitar Studi Kasus : Perumahan Menengah Atas di Yogyakarta - Maria Immaculata Ririk Winandari; Bambang Hari Wibisono; Achmad Djunaidi; Heddy Shri Ahimsa-Putra (Forum Teknik, 2013)
Upper middle-class housing has been growing fast in Yogyakarta, most of these being exclusive estate with limited acces. There has been curiosity that this condition minimizes interaction between in habitants of  housing estate and people in the surrounding area. Therefore, the purpose of this study was to examine the relatianshif  between housing layout, inhabitants’ interaction, and people in the surrounding area. The study was conducted in four Yogyakarta’s housing estate representhing the upper middle-class income community, they are Pertamina Complex Estate, Nandan Griya ldaman Estate, Griya lntan Permai Estate and Casa Grand Estate. The case study method was used to establish the relatianshif  between housing layout and inhabitants’ interaction through comparison of cases. The results of the study show that the number of  housing entrances, public, and commercial facilities as well as the obscure physical boundaries influence the interaction among inhabitants of  housing estate and people in the surrounding area. The high expectation of safety, security warranty, and the housing surveillance minimised the interaction between in habitants of  housing estates and people in the surrounding area eenwendfng ered. The design af the estates that enables local people to use the estates' facilities contributed to the increased interaction between inhabitants of  housing estate and people in the surrounding area.Keywords:  housing layout, public open space, interaction, upper midd/e-class, Yogyakarta